Power Relations in Local Democracy: An Analysis of the Position of BPD and Village Heads in the Indonesian Constitutional System: Relasi Kekuasaan dalam Demokrasi Lokal: Analisis Kedudukan BPD dan Kepala Desa dalam Sistem Ketatanegaraan Indonesia - Adhe Ismail Ananda; Fadli Maulana; Muh. Taqwin Tahir; Rahmat Angga Dwi Putra (Journal of State Democracy, 2025)
Village democracy is the embodiment of people's sovereignty guaranteed in Law Number 6 of 2014 concerning Villages. BPD is presented as a community representation institution that functions deliberative and supervises the Village Head as an executive. However, in practice, the role of BPD is often ineffective because the election process is often intervened by the Village Head, even the membership is dominated by people close to the village executive. As a result, BPD more often acts as a policy "stamp" rather than carrying out a supervisory function. This study uses a normative juridical method with a legislative and conceptual approach. The results of the study show that the relationship between BPD and Village Head is still uneven, with the dominance of village executives and weak BPD independence. This condition lowers the quality of local democracy and weakens the principle of checks and balances. Therefore, it is necessary to strengthen the BPD election mechanism, increase institutional capacity, and participatory supervision for a more accountable village democracy.